Flower-Like ZnO Nanorods Synthesized by Microwave-Assisted One-Pot Method for Detecting Reducing Gases: Structural Properties and Sensing Reversibility - Aljaafari, Abdullah; Ahmed, Faheem; Awada, Chawki; Shaalan, Nagih M. (Frontiers in Chemistry, 2020)
In this work, flower-like ZnO nanorods (NRs) were successfully prepared by microwave-assisted techniques at a low temperature. The synthesized NRs exhibited a smooth surface and good crystal structure phase of ZnO. The sharp peak of the XRD and Raman spectrum confirmed the high crystallinity of these ZnO NRs with pure wurtzite structure. The nanorods were ~2 μm in length and ~150 nm in diameter, respectively. The electron diffraction pattern confirmed that the single crystal ZnO nanorods aligned along the [001] plane. The NRs were applied to fabricate a gas sensor for reducing gases such as CH4, CO, and H2. The sensor showed a food performance and sensitivity toward the target gases. However, its response toward CH4 and CO was higher compared to H2 gas. Although the operating temperature was varied from room temperature (RT) up to 350oC, the sensor did not show response toward any of the target gases in the range of RT-150oC, but dramatic enhancement of the sensor response was observed at 200oC up to higher temperatures. This behavior was ascribed to the activity of the smooth surface and the reactivity of surface oxygen species with the targeted gases. The sensor response was measured at various gas concentrations, where the calibration curve was shown. The gas sensing mechanism was described in terms of the reaction of the gases with the transformed oxygen species on the surface of the oxides.